The influence of eHealth literacy, reproductive health knowledge, and self-esteem on health-promoting behaviors in early adult women: a cross-sectional survey - Hye Sook Shin; Young A Song (Korean Journal of Women Health Nursing, 2022)
Purpose The purpose of this study was to investigate the influence of eHealth literacy, reproductive health knowledge, and self-esteem on early adult women’s health-promoting behaviors (HPB). This study was based on Pender’s health promotion model as a theoretical underpinning. Methods Early adult women aged 18 to 35 years (n=165) were recruited by posting advertisements on social network sites for a student club and a faith-based community in Ansan, Korea. Willing individuals were invited to participate in the online survey from June 1 to June 30, 2022. Standardized instruments were used to measure HPB, eHealth literacy, reproductive health knowledge, and self-esteem. General characteristics included income level, perceived subjective health, and internet usage time. The collected data were analyzed using the independent t-test, one-way analysis of variance, Pearson correlation coefficients, and multiple regression. Results The mean age of the respondents was 21.97±3.87 years. The total HPB score was 120.69, corresponding to a moderate level; and the total scores for eHealth literacy (30.24), knowledge of reproductive health (23.04), and self-esteem (35.62) were higher than the midpoint. The model explained 53.3% of variance in HPB, and self-esteem (β=.48, p<.001) was the most influential factor. Other influential factors were, in descending order, higher economic level, higher subjective health status, greater eHealth literacy, and less internet use time (<2 hours/day). Conclusion In order to promote the health of early adult women, counseling or programs that positively improve self-esteem appear promising, and eHealth literacy should be considered as a way to promote HPB using information technology.